Extubación precoz es una alternativa para disminuir el riesgo de contaminación nosocomial en pacientes 0- 4 años con cardiopatías postquirúrgicas, Hospital Roberto Gilbert. Guayas. octubre 2018 – abril 2019 - Recalde Sánchez, Maité Alejandra (2019)
Early extubation is post-surgical cardiological patient is given to the first 6 hours of surgery, it is considered an alternative for the reduction of nosocomial contamination, because long days of endotracheal intubation patients will be exposed to pathogenic microorganisms producing a high risk of mortality, and other risk factors. This research project seeks to demonstrate and ensure that the technique is effective and prevent nosocomial or in-hospital contamination, decrease direct respiratory infections, as other benefits we will reduce costs and hospital stays, will provide a better quality of life to the patient. The objective of the research is to obtain the results through a deductive methodology, allowing us to study the problem of the subject, achieving as a result an alternative solution. Likewise, field research was used where direct contact was made with the patients and the risks of late extubation, complications and failure of extubation were observed; Within the results, tables were made in which it was demonstrated that the technique is a benefit for patients with congenital cardiopathies recently operated; the graphs are formed with the behavior of the most important variables in this project such as: weight, age, symptoms, success and failure of early extubation. In order to give recommendations and improvements for the health status of babies and children.